Find the quotient.
(6x^2 - x - 40) ÷ (5 + 2x)

(6x^2 - x - 40) ÷ (5 + 2x) = (6x^2/5 + 2x) - (x/5 + 2x) - (40/5 + 2x) = 3x - 8

Question

Asked 6/20/2013 9:18:59 AM

Updated 11/21/2016 10:21:21 PM

1 Answer/Comment

Edited by Andrew. [11/21/2016 10:20:43 PM]

Rating

3

(6x^2 - x - 40) ÷ (5 + 2x)

= (6x^2/5 + 2x) - (x/5 + 2x) - (40/5 + 2x)

= 3x - 8

= (6x^2/5 + 2x) - (x/5 + 2x) - (40/5 + 2x)

= 3x - 8

Added 11/21/2016 10:21:21 PM

This answer has been confirmed as correct and helpful.

What is the solution set of (x - 2)(x - 3) = 2?

Question

Expert Answered

Updated 5/26/2014 8:16:37 PM

1 Answer/Comment

Choose the product.(5x2 + 2x - 3)(x - 1)

Question

Expert Answered

Updated 8/19/2014 12:58:44 AM

1 Answer/Comment

(5x^2 + 2x - 3)(x - 1)

= 5x^3 - 5x^2 + 2x^2 - 2x - 3x + 3

= 5x^3 - 3x^2 - 5x + 3

= 5x^3 - 5x^2 + 2x^2 - 2x - 3x + 3

= 5x^3 - 3x^2 - 5x + 3

Added 8/19/2014 12:58:44 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/19/2014 1:06:35 AM]

Factor 25x2 + 10x + 1. **Weegy:** 25x^2 + 10x + 1 = (5x + 1)^2 (More)

Question

Expert Answered

Updated 7/16/2014 4:58:27 AM

0 Answers/Comments

27,098,482

questions answered

There are no comments.